2022
DOI: 10.31234/osf.io/sq9vw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No correlation between articulation speed and silent reading rate when adults read short texts

Abstract: Silent reading often involves phonological encoding of the text in addition to orthographic processing. A question related to the phonological code concerns its richness: Is it an abstract code or does it contain information about the pronunciation of the visual stimulus? To answer this question, we investigated the relationship between articulation speed and reading speed, both for silent reading and reading aloud. We investigated whether people with fast articulation speed read faster than people with slow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Vasilev et al (2022) reported a reading rate of 165 words per minute (SD = 50) in participants reading short non-fiction paragraphs word-by-word. 1 This is slower than the typical reading rate for non-fiction texts (240 words per minute; Brysbaert, 2019), but still as fast as listening to speech (Brysbaert & Vantieghem, 2023).…”
Section: A Call To Build An Expanding Eye Movement Database By Provid...mentioning
confidence: 99%
“…Vasilev et al (2022) reported a reading rate of 165 words per minute (SD = 50) in participants reading short non-fiction paragraphs word-by-word. 1 This is slower than the typical reading rate for non-fiction texts (240 words per minute; Brysbaert, 2019), but still as fast as listening to speech (Brysbaert & Vantieghem, 2023).…”
Section: A Call To Build An Expanding Eye Movement Database By Provid...mentioning
confidence: 99%